KEPENTINGAN AMERIKA SERIKAT SEKTOR PERMINYAKAN DI INDONESIA MELALUI PERUBAHAN UU MIGAS NO. 8 TAHUN 1971 MENJADI UU NO. 22 TAHUN 2001 - Ardian Mustofa (Jurnal Studi Diplomasi dan Keamanan, 2018)
Amendment of the Oil and Gas Law No. 8 of 1971 to becomeLaw No. 22 of 2001 shows the interests of the United States, namely the interests to accommodate interest groups. The existence of the United States as a democratic country has a character in policy making, namely considerations in policy aggregation that must be able to accommodate the interests of political parties, to capitalist and industrial groups. The United States economic - political entity then attempts to make the energy management system in Indonesia towards liberalism so that it can support the achievement of the United States national interests in the long term. United States interests through United State Agency of International Development(USAID) in the amendment of Law No. 8 of 1971 became Law No. 22 of 2001 is to strengthen economic - political capacity and energy security. The United States is an industrial country that is highly dependent on petroleum energy. The United States has long been dependent on world oil production, so the country is trying to implement a variety of strategies, including double standards in the Middle East region which have been the main supplier of US oil needs. When this region experiences economic tensions and conflict, the United States will look for areas that can still support energy availability, including Indonesia. United States interests through USAID assistance program to amend the Oil and Gas Law No. 8 of 1971 became No. 22 of 2001 will be fully discussed in this thesis.